Convex nonparametric least squares and stochastic semi-nonparametric frontier to estimate the shadow prices of PM2.5 and NOx for Taiwan's transportation modes. Issue 9 (12th July 2021) - Chen, Huey-Kuo; Lin, Yi-Hsiu; Lee, Chia-Yen
Abstract: With the growing environmental awareness, people are concerned about the air pollution issues because these issues not only cause adverse environmental effects but also damage human's health conditions. Most of previous studies estimating the shadow prices of emissions mainly focused on stationary sources (e.g. coal-fired power plants) rather than mobile sources; however, traffic is one of critical emission sources. This paper uses convex nonparametric least squares (CNLS) and stochastic semi-nonparametric envelopment of data (StoNED) to estimate the shadow prices of PM2.5 and NOx for eleven transportation modes in seven air quality areas in Taiwan in 2013. We find that their shadow prices for two-stroke and four-stroke scooters are indifferent, and infer that it is unnecessary to develop different emissions policies for these transportation modes. However, the shadow prices for gas-fuelled vehicles which are relatively high and thus we suggest mandating advanced emissions technology or retrofits, or subsidies for electric vehicle replacements of this transportation mode. The significant distinctions in the corresponding shadow prices of PM2.5 and NOx we find for eleven transportation modes in Taiwan's seven air quality areas indicate that policy-makers and regulators consider a variety of mitigation approaches.